Factors that Affect Calf Selling Price at Marketing - Matt Hersom; Todd Thrift (EDIS, 2012)
There are differences between the real and perceived reasons that cattle buyers discount calves; cattle producers can control some reasons for price differentials, but they cannot control all of them. This 4-page fact sheet will review some of the attributes that affect market calf price and overall value. Written by Matt Hersom and Todd Thrift, and published by the UF Department of Animal Science, May 2012.